Tata Kelola Sumber Daya Keuangan Di SMAN 13 Bandung - Yudi Ruswandi; Ahmad Dini; Irwan Sutiawan (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This research is motivated by the fact that SMAN 13 Bandung is one of the outstanding educational units. Reflected in several achievements from the principal to the students. In addition, this school has developed into a very qualified school. The purpose of this study is to describe the planning, implementation and financial reporting processes at SMAN 13 Bandung. The research procedure includes pre-field, field and data analysis activities. Data collection techniques consist of: interviews, observation, and documentation studies. The result of this study is that the governance of financial resources has been carried out in accordance with management principles in planning, implementing and reporting on the use of the budget in accordance with applicable regulations. Based on the results of these studies, the conclusion of this study is that SMAN 13 Bandung has realized good financial management. In accordance with the results of the research, the recommendations for this research are: first, schools can confirm school priority programs based on the results of context analysis; second, encouraging the implementation of concrete steps regarding alternative solutions to problems as stated in the Medium Term Activity Plan (RKJM) document